COMPLETE METHOD OF REMOVAL OF DRILLING PULLEY SIDE RINGS - Havryliv, Yu. L.; Pitulei, L. D.; Havryliv, S. Yu.; Ступар, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
An integrated method of restoring worn rims of pulleys without dismantling, which combines surfacing, profiling and installation in a profiled rim of the movable lining, is offered. The design of the needle milling device has been developed. A mathematical model of the dependence of the cutting power of a needle cutter on the cutting speed is constructed. The adequacy of the model with the experimental data is verified. The output formula of the needle milling device is shown. Recommendations are given for designing the profile of the cutting part of the needle cutter. The proposed design of the mobile lining, made of separate lining elements on elastic flexible links. The design of a tension device for compensation of elongation of flexible links is offered.